Romania : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Romania. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2017)
This 2017 Article IV Consultation highlights Romania's strong economic growth in 2016, resulting in a closed output gap. Private consumption was boosted by an expansionary and procyclical fiscal policy and wage increases. The cyclically adjusted budget deficit grew by 1.5 percent of GDP in 2016, reflecting large tax rate cuts and wage increases. Headline inflation remained subdued owing to indirect tax cuts, administrative price adjustments, and low euro area inflation and oil prices. There has been welcome progress in reducing banking sector nonperforming loans. Growth is expected to reach 4.2 percent in 2017 and to moderate to 3.5 percent in the medium term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet